Kajian Sosiologi Sastra Pada Naskah Hikayat Si Orang Gila Karya Eka Kurniawan dalam Antologi Cerpen Corat-Coret di Toilet dengan Berbagai Permasalahannya Sebagai Bahan Ajar Materi Drama Jenjang SMP Kelas 8 - Resti Sri Monika; Elsa Sri Lunawati; Zubaedah Mahdiyah; Adita Wirada Putra (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2024)
The aim of this research is to describe how people's lives are described by the author in the short story Scribbles on the Toilet by Eka Kurniawan. Researchers use descriptive analysis methods by analyzing based on the facts contained in the short story. Data collection uses the reading-note technique which is used to obtain data by reading, understanding and recording quotations that are in accordance with the formulation of the problem. The results of the research show that there are phenomena in community life that are currently occurring.